2009
DOI: 10.1152/japplphysiol.90756.2008
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise training reduces epicardial fat in obese men

Abstract: The purpose of this study was to determine the effects of exercise training on ventricular epicardial fat thickness in obese men and to investigate the relationship of the change in epicardial fat thickness to changes in abdominal fat tissue following exercise training. Twenty-four obese middle-aged men [age, 49.4 +/- 9.6 yr; weight, 87.7 +/- 11.2 kg; body mass index (BMI), 30.7 +/- 3.3 kg/m(2); peak oxygen consumption, 28.4 +/- 7.2 ml.kg(-1).min(-1); means +/- SD] participated in this study. Each participant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(101 citation statements)
references
References 47 publications
6
91
2
2
Order By: Relevance
“…Weight loss by caloric restriction, 37 exercise, 38 or bariatric surgery 39 in obese patients leads to significant reductions (9%-32%) in epicardial fat thickness. Pharmaceutical treatments associated with thinner epicardial fat target either lipid metabolism or glucose homeostasis.…”
Section: Conclusion: Therapeutic Implications and Future Directionsmentioning
confidence: 99%
“…Weight loss by caloric restriction, 37 exercise, 38 or bariatric surgery 39 in obese patients leads to significant reductions (9%-32%) in epicardial fat thickness. Pharmaceutical treatments associated with thinner epicardial fat target either lipid metabolism or glucose homeostasis.…”
Section: Conclusion: Therapeutic Implications and Future Directionsmentioning
confidence: 99%
“…The results of other large studies have revealed that the degree of coronary calcification correlates with the amount of pericardial fat, and that this correlation predicts progression of atherosclerosis in subjects with low calcification followed from the outset 7 . Increased number of macrophages, T-lymphocytes and mast cells in epicardial fat but not in SAT have been demonstrated in patients with coronary artery disease by several researchers independently 8,9 and regression of epicardial fat has been observed in relation to weight reduction 10 , exercise 11 or following administration of either atorvastatin 12 or ezetimibe 13 . Whether this reduction leads to a decreased cardiovascular risk remains unclear and needs to be further examined.…”
Section: Fat Depots: Perivascular Epicardial Visceral and Subcutaneousmentioning
confidence: 99%
“…Furthermore, the LM and FM of footballers and judokas were similar. Physical activity is one of fat mass reduction [31] . Thus, the decrease of FM was confirmed by our study in footballers and judokas compared to controls.…”
Section: Discussionmentioning
confidence: 99%